PENGEMBANGAN QUARTET MATHEMATICS CARD BERBASIS BUDAYA ACEH PADA MATERI BANGUN DATAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN LAMLHOM - Nabila, Nur'ain; Nasriadi, Ahmad; Subhananto, Aprian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student learning outcomes in mathematics for Class V remain low, particularly in the flat shapes material, due to the limited use of innovative and engaging learning media. This study aims to: (1) describe the development process of the Quartet Mathematics Card learning media based on Acehnese culture for flat shapes material for Class V students at SDN Lamlhom; (2) describe the validity and practicality of the media; and (3) determine its effectiveness in improving student learning outcomes. This study employed the Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 22 Class V students at SDN Lamlhom. Data were collected through questionnaires, interviews, tests, and documentation. The results show that: (1) the media was developed through five systematic ADDIE stages; (2) the media was rated highly valid with a validity percentage of 99.22% and highly practical with a practicality percentage of 95.59%; and (3) the media was highly effective in improving student learning outcomes, as indicated by a classical mastery rate of 90.91% and an N-Gain value of 0.76, categorized as high, with an effectiveness percentage of 76.77%.